Heretical necessity: Herman Melville and the fictions of charity - Harrison, Colin (1997)
Heretical Necessity explores the various ways in which an idea of value was established and debated through the literature of mid 19th century America. Above all, it concerns moral value, the language of personal virtue and social ethics; this includes notions of sympathy and self-sacrifice promoted in sentimental fiction, which I read alongside Melville's responses in his later work: the perversion of altruism in Pierre, his critique of benevolence in the short stories, and his ironization of trust in The Confidence Man. Charity is a key issue because it refers both to a notion of fellowship integral to the sentimental vision of society and to a principle of unreciprocated (hence antagonistic) action: giving one's all becomes incompatible with the more measured principles of justice on which a democracy has to be based.